"3 + 1 = 6 + 2" in Cu(ii) coordination chemistry of 1H-pyrazole aza cryptands1. Issue 7 (21st February 2015) - Pitarch-Jarque, Javier; Belda, Raquel; Lloret, Francesc; Ferrando-Soria, Jesús; Navarro, Pilar; Lopera, Alberto; García-España, Enrique
<x xml:space="preserve">Abstract</x> We report the first example of a cryptand able to form 6 + 2 Cu(ii)-ligand dimeric hexanuclear complexes, both in the solid state and in aqueous solution, by simply combining the metal and the ligand in a 3 : 1 molar ratio.